Eduardo José Míguez, Bartolomé Mitre, entre la Nación y la Historia, Buenos Aires, Edhasa, 2018, pp. 448 - Bussani, Gerardo (2018)
Fil: Bussani, Gerardo. Pontificia Universidad Católica Argentina; Argentina